Odpowiedź :
Odpowiedź:
A) 5^6 * 5^2 * 5^4 = 5^6+2+4 = 5^12
B)7^2 * 7^5 * 7 = 7^2+5+1 = 7^8
C) 3^4 * 3 * 3^5 = 3^4+1+5 = 3^10
D) 2 * 2^5 * 2^8 = 2^1+5+8 = 2^14
E) 4 * 4^2 * 4^9 = 4^1+2+9 = 4^12
F) 6^2 * 6^5 * 6^8 = 6^2+5+8 = 6^15
Odpowiedź:
Hej!
a)
[tex]5^{6} *5^{2} *5^{4} =5^{12}[/tex]
b)
[tex]7^{2}*7^{5} *7=7^{8}[/tex]
c)
[tex]3^{4} *3*3^{5}=3^{10}[/tex]
d)
[tex]2*2^{5}*2^{8}=2^{14}[/tex]
e)
[tex]4*4^{2}*4^{9}=4^{12}[/tex]
f)
[tex]6^{2}*6^{5}*6^{8}=6^{15}[/tex]
Pozdrawiam-~Gabriela :)
Szczegółowe wyjaśnienie:
Wystarczy że dodasz potęgi a jeśli jest liczba bez potęgi to poprostu jest to jak np.
7 do potęgi 1